National Income Inequality and International Business Expansion. Issue 8 (November 2020) - Lupton, Nathaniel C.; Jiang, Guoliang Frank; Escobar, Luis F.; Jiménez, Alfredo
We examine the extent to which host country income inequality influences multinational enterprises' (MNE) expansion strategy for foreign production investment, depending on their specific strategic objectives. Applying a transaction cost framework, we predict that national income inequality has an inverted U-shaped relationship with foreign production investment. As inequality increases, MNEs accrue lower transaction costs arising from interactions with various local actors, leading to higher probability of investment. As income inequality increases further, its effect on location attractiveness will become negative, as its attraction effect is increasingly offset by additional monitoring, bargaining, and security costs owing to the more fractious nature of high inequality societies. In addition, we suggest that the impact of income inequality is contingent on investment objectives: The inverted U-shaped relationship is stronger for efficiency-seeking investment but weaker for market-seeking and competence-enhancing investments. We find substantial support for our hypotheses through an analysis of 27 years (1986-2012) of data on Japanese MNEs' overseas production entries.